The Effect of Skill Exercises According To the Properties of the (Strength-Time) Curve in the Development of Scoring Performance for Soccer Players Ages (13-14) Years - Shakir Rzaej, Wisam; Abdul Hameed Shblan, Fahad; Oudah Gshayyish, Khalid (International Journal of Psychosocial Rehabilitation, 2020)
The use of modern scientific theories of science related to the sports side has had a profound impact on the development of the sports level in all events and sports where many changes and adjustments have been made to various training methods to ensure positive developments in the direction of training requirements and physical, skill and planning competitions. One of the main duties of training is to reach the athlete up Level and that the difference games are one of the most famous games in the world, they also need a lot of this development, although they have made great efforts in order to reach advanced positions in the championships, and accordingly, preparing teams requires keeping up with this development and modern scientific progress, so it has become associated with many sciences others include training science, learning, physiology, biomechanics, and sports psychology.